The Effect of Internal Training and Auditing of Auditors on Supply Chain Management: An Empirical Study in Listed Companies of Iraqi Stock Exchange for the Period 2012-2015 - Salim Awad Hadi Alzabari; Hassnain Raghib Talab; Hakeem Hammood Flayyih (International Journal of Supply Chain Management, 2019)
This study aimed to examine the joint effect of auditor’s auditing and training on reducing financial statements’ manipulation Iraqi companies listed in stock exchange. Specifically, this study focuses on the impact of internal training and auditing of internal audit staff on reduction of the rate of manipulation in earnings management practices as depicted by the discretionary accruals. The financial statements for 69 listed companies in the Iraqi Stock Exchange were analyzed in this study in order to achieve these objectives for the period of 2012-2015. The earnings management which is measured by the Kothari et al. model (2005) is the dependent variable while independent variables considered in this study are auditor’s training and the internal audit. The independent variables are analyzed using a set of data gathered from the selected companies. Based on the results of study recommends the need for activating the internal control bodies which shall consider the requirements necessary before publishing financial statements in the market by the listed companies in the Iraqi stock exchange. The requirements are also necessary to be connected with the audit committees of the companies and more training courses should be conducted for the auditors. This research can be used for the universities, teachers and students. In this research, the model of the The effect of internal training and auditing of auditors on Earning Management is presented in a comprehensive and complete manner.